PARTES INTEGRALES JAKO PODSTAWA TŁUMACZENIA CNOTY ROZTROPNOŚCI W TRADYCJI PERYPATETYCKIEJ - Gondek, Maria Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The functioning of prudence is characterized by following parts: integral, subjective, and potential. Fundamental importance for prudence have its integral parts. St. Thomas Aquinas treated them as constituting the virtue of prudence. They have the essential character. Their existence is necessary to achieve a perfect act (perfectum actum) of virtue. Thus it is not possible to explain prudence without taking into account its structure, pay attention to the integral parts. The factor of actualization and perfection, whereby prudence is realized, decided about crucial character of its integral parts.